Application of Design Thinking for Innovation in Banking - Jirli, Poornima (Digital Repository of Theses - SSBM Geneva, 2024)
This thesis presents a comprehensive analysis of the adoption and influence of design thinking in the banking sector, emphasising its role in driving innovation and strategic decision-making. This study employed a dual methodology approach. To map the existing landscape, it utilises bibliometric analysis per PRISMA, identifying key literature trends and gaps. This phase aimed to provide a macro-level understanding of the evolution and status of design thinking in the banking sector. An empirical examination uses a Partial Least Squares Structural Equation Model (PLS-SEM) grounded in Behavioral Reasoning Theory (BRT). Using this approach, operational insights are gained from exploring how bank professionals perceive the benefits and barriers of design thinking. This is done by examining how they comprehend and incorporate them into their organizational strategies. The empirical analysis provides compelling evidence that the benefits of design thinking significantly correlated with a deeper understanding of its methodologies among banking professionals. The study also revealed the essential impact of perceived barriers on resistance to design thinking. This may have affected the missed opportunities and strategic planning. The research concludes that design thinking can significantly propel strategic innovation in banking when adequately understood and aligned with organisational strategies. This underscores the potential of design thinking as a transformative force that can redefine traditional banking paradigms and foster a more innovative and adaptive industry. This thesis contributes to academic discourse by providing a macro and micro perspective on design thinking in banking, bridging the gap between theoretical understanding and practical application. This is a foundational resource for scholars and practitioners aiming to leverage design thinking for strategic advantage in the dynamic banking world.